Integrated approaches to the optimisation of regional and local food-energy-water systems - Veldhuis, A; Yang, A (Elsevier, 2017)
Optimisation of regional and local food-energy-water systems that takes into account the connections between the three sectors is classified into “integration based on footprint” and “integration based on co-decision”. Footprint-based approaches focus on the decision on one main system while using static footprint data to account for the links with other systems. In contrast, co-decision based approaches aim to simultaneously optimise multiple, interconnected systems. Choosing between these two approaches needs to consider the nature of the interactions between different systems as well as data availability and the feasibility of implementing the optimisation results. Future research in this area is expected to broaden decision targets and to improve the handing of the multiple scales involved in integrated food-energy-water decision making.